2018
DOI: 10.2174/1381612824666180130115153
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Molecular Imaging in Inflammatory and Autoimmune Disorders

Abstract: In the field of inflammation imaging, nuclear medicine techniques can be considered as a non-invasive tool to early detect pathophysiological changes in affected tissues. These changes usually occur before clinical onset of symptoms and before the development of anatomical changes, that are commonly detected by radiological procedures. This is particularly important for prognostic purposes, therapy decision making and for therapy follow-up. Here we review the current state-of-the art of nuclear medicine for di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Uptake of this tracer is relatively higher in cells that are metabolically active, such as inflammatory cells. FDG is indicated in several infectious and inflammatory diseases and is useful for the diagnosis and follow-up of various autoimmune diseases [ 4 , 101 , 102 ]. In pSS patients, several case reports showed abnormal FDG uptake in salivary glands [ 103 , 104 , 105 ] ( Figure 5 ).…”
Section: Nuclear Medicine Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Uptake of this tracer is relatively higher in cells that are metabolically active, such as inflammatory cells. FDG is indicated in several infectious and inflammatory diseases and is useful for the diagnosis and follow-up of various autoimmune diseases [ 4 , 101 , 102 ]. In pSS patients, several case reports showed abnormal FDG uptake in salivary glands [ 103 , 104 , 105 ] ( Figure 5 ).…”
Section: Nuclear Medicine Techniquesmentioning
confidence: 99%
“…It has been shown that imaging techniques can assist in the diagnostic process of pSS [ 3 ]. Imaging techniques could also be of value in assessing disease activity and detecting disease progression in pSS, which has already been shown in other systemic autoimmune diseases [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two peptide‐based radiopharmaceuticals targeting VCAM‐1 ( 99m Tc‐B2702‐p and 18 F‐4V) were initially developed, and both of the tracers were seen to accumulate in atherosclerotic plaques in preclinical animal models. Even though they showed high affinity for VCAM‐1 and good correlation with the expression levels of inflammatory genes such as CD68, a biomarker of macrophages in inflammatory atherosclerosis, clinical use of these tracers is still limited …”
Section: Targeting Cell‐adhesion Moleculesmentioning
confidence: 99%
“…Currently, several radiopharmaceuticals have been developed and used for the diagnosis of chronic inflammatory diseases in the clinic. For example, radiolabeled white blood cells such as 99m Tc‐hexamethylpropyleneamine oxime (HMPAO)‐labeled leukocytes have been commonly used to monitor the migration of immune cells into inflamed sites of IBD or RA . Although 99m Tc‐HMPAO‐labeled leukocytes can detect the extent of disease with high sensitivity, this strategy has disadvantages because the ex vivo‐labeling techniques are cumbersome, and it is hard to achieve long‐term observation of cell viability with this method …”
Section: Introductionmentioning
confidence: 99%
“…The combination of radiological imaging modalities, such as ultrasound (US), computed tomography (CT) and magnetic resonance imaging (MRI) NM techniques, comprising single photon emission computed tomography (SPECT) and positron emission tomography (PET) might allow us to analyse which target molecules are expressed at which location, to make an early diagnosis, and to decide the best therapy in a diversity of pathologies. Thus, several radiopharmaceuticals may be used in relation to the complex and various pathways involved in the diseases [1,2].…”
Section: Introductionmentioning
confidence: 99%